International journal of enterprise information systems (IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2005)
The primary objective of the International Journal of Enterprise Information Systems (IJEIS) is to provide comprehensive coverage and understanding of various enterprise information systems (EIS) such as enterprise resource planning (ERP) and electronic commerce (EC) and their implications on supply chain management and organizational competitiveness. Design, development, and implementation issues of EIS including ERP and EC will be discussed. These include organizational, people, and technological issues of EIS. The secondary objective of this journal is to expand the knowledge on ERP and EC and in turn help researchers and practitioners to develop suitable strategies, tactics, and operational policies for EIS and for improving communication in organizations. This journal publishes original contributions in the areas of design and implementation of EIS. IJEIS intends to be a forum for exchanging new ideas and developments in the field of EIS. This journal also acts as a medium of communication among EIS researchers and practitioners.